The Mediatization and Culture Of The Korean Wave Phenomenon Among Malay Female Youth - Nurul Akqmie Badrul Hisham; Abdul Latiff Ahmad; Chang Peng Kee (Ikatan Sarjana Komunikasi Indonesia, 2022)
The development of media technology became a key element in constructing social realities. This study analyses the process of mediatization in contemporary youth culture and how social media has played a role in creating the mediated world. Aiming to explore the mediated world of Korean Wave female fans in Malaysia using the perspective mediatization and culture. This study was conducted using qualitative research and a netnography was conducted due to the movement control orders or locked downs that took place in many countries due to the Covid-19 pandemic.Â The study was conducted on events that took place on the Internet. This study shows social media as a catalyst in connecting fans with the social phenomenon and it has allowed fans to create their own mediated world and online community. The mediazation process bring fans and celebrities closer to each other with information on the Korean Wave obtained without interruption and filtering. Social media had led to negotiation creations of social reality, the empowerment of groups involved and these groups participation in the evolution of the Korean Wave becomes an essential part of the phenomenon.